DARKNET BROWSERS: TYPES, CAPABILITIES AND THEIR USE IN CRIMINAL ACTIVITIES (International journal of artificial intelligence, 2024)
This article explores darknet browsers as tools for accessing the anonymous darknet network, their types (Tor, I2P, Freenet), working principles, and technical features. It focuses on the opportunities these browsers offer for both legitimate activities (freedom of speech, privacy protection) and criminal ones (drug trafficking, weapons trade, cybercrime). The use of darknet browsers for illegal purposes and counter-measures against this activity are analyzed.